Augmentative and alternative communication in autism spectrum disorder: transitioning from letter board to iPad – a case study - Mavritsakis, Dionisia (Frontiers in Psychiatry, 2024)
This case study examines the effective use of Augmentative and Alternative Communication (AAC) tools in enhancing communication skills in a 15-year-old male with Autism Spectrum Disorder (ASD). Initially exhibiting non-verbal tendencies, the subject experienced significant improvements in communication and social interaction following the introduction of a letter board and subsequent transition to an iPad. These AAC tools facilitated a marked development in his ability to articulate thoughts, engage in academic activities, and express complex ideas, particularly in science. The study highlights the role of AAC in expanding the communicative capabilities of individuals with limited or no verbal language , demonstrating notable advancements in both verbal expression and cognitive engagement. The findings underscore the transformative impact of personalized AAC interventions and suggest the potential for broader application in ASD support strategies. This case highlights the need for further research, including randomized controlled trials, to explore the efficacy of AAC tools in diverse ASD contexts.